"Abun" (Elegi Seorang Ayah): Analisis Struktural Model Farhud - . Sangidu (Humaniora, 2008)
This paper aims at revealing the intrinsic aspect of the poem "Abun" (Elegy of a Father) and the inter-relationships among its aspects to discover the total meaning of the poem. The aspects include al-ma'nâ (ideas), al-'âthifah (emotion), al-khayyâl (imagination), lughatusy-syi'ir (language of poetry), and mȗsiqasy-syi'ir (rhyme and intonation).The meaning of the poem is to depict the sadness of a father because of being separated from his children. The sweet and bitter memories he has when he is with them is hard to forget. He always remembers the time when his children often argue with one another, cry and laugh together and compete with one another. All these he has to leave behind because his children have grown up and become independent.